2014
DOI: 10.3109/19401736.2014.971297
|View full text |Cite
|
Sign up to set email alerts
|

Complete mitochondrial genome sequence of Piaractus mesopotamicus (Holmberg, 1887)

Abstract: The migratory species Piaractus Mesopotamicus, popularly known as the pacu, was determined to have a complete mitochondrial genome of 16,722 bp with 45% GC content. The genome contained 13 protein-coding genes (PCGs), 2 rRNA genes, 22 tRNA genes, and a 1048 bp Control Region (D-loop). Almost all the PCGs used the standard ATG start codon, except for Cox1 that used a GTG start codon. Five of the 13 PCGs had a TAA stop codon, two had the incomplete stop codon TA- (Atp6 and Cox3), and five had the incomplete stop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…Only five out of 13 PCGs (ND1, ND2, ATPase8, ND4L and ND5) contained a TAA stop codon; four (COII, ND3, ND4 and Cytb) displayed incomplete termination codon (T-); three genes (ATPase6, COIII and ND6) displayed the incomplete TA-stop codon. Only COI presented AGG as stop codon, similar to others Characiformes (Siqueira et al 2014;Brandão-Dias et al 2016;Pimentel et al 2016); considered a vertebrate evolution (Osawa et al 1989). …”
supporting
confidence: 69%
See 1 more Smart Citation
“…Only five out of 13 PCGs (ND1, ND2, ATPase8, ND4L and ND5) contained a TAA stop codon; four (COII, ND3, ND4 and Cytb) displayed incomplete termination codon (T-); three genes (ATPase6, COIII and ND6) displayed the incomplete TA-stop codon. Only COI presented AGG as stop codon, similar to others Characiformes (Siqueira et al 2014;Brandão-Dias et al 2016;Pimentel et al 2016); considered a vertebrate evolution (Osawa et al 1989). …”
supporting
confidence: 69%
“…The mitochondrial genome of L. elongatus was 16,784 bp (GenBank KU980144) solved with 205.16 folds of coverage. The GC content of the total sequence was 43%, with individual base content being: 29.9% A, 15.7% G, 27.1% T and 27.3% C. The mtDNA genome contains 2 rRNA and 22 tRNA genes, 13 protein-coding genes (PCGs) and a control region (D-loop) with 1115 bp, being consistent with mitochondrial genome structure of the fishes Carmo et al 2016;Chagas et al 2016;N uñez-Rodriguez et al 2016;Pimentel et al 2016;Resende et al 2016;Siqueira et al 2014). Only gene COI started with GTG codon, differing from all other PCGs that display the usual start codon ATG.…”
supporting
confidence: 66%
“…Read representation was evaluated by mapping the cleaned reads back to generated assembly with BOWTIE2 v.2.3.4.3 (Langmead and Salzberg, 2012). A. hydrophila genome (Yang et al, 2016), zebrafish ribosomal RNA (rRNA) sequences and pacu mitochondrial genome (da Pimentel et al, 2014) were then downloaded from the NCBI (National Center for Biotechnology Information) database and mapped against the assembly using BOWTIE2 v.2.3.4.3 (Langmead and Salzberg, 2012) to remove any contamination. Redundancy was reduced using CD-HIT-EST v.4.6.8 software by clustering sequences at 95% identity (Li and Godzik, 2006).…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…Studies of vertebrate species have shown a mutation rate that exceeds, by multiple times, nuclear DNA mutation rates that may be due to a lack of repair mechanisms during replication [116]. The complete mtDNA sequences have been sequenced to facilitate analyses of molecular markers in many economically important Neotropical fish species, such as S.brasiliensis [117], P. mesopotamicus [118] and L. elongatus [119].The DNA of cytoplasmic organelles has a non-Mendelian inheritance, and the mtDNA must be considered a single locus in genetic investigations [94]. Inheritance occurs via the mitochondria of the oocyte from which an animal develops [120].…”
mentioning
confidence: 99%